Manipulating Halide Perovskite Passivation by Controlling Amino Acid Derivative Isoelectric Point for Stable and Efficient Inverted Perovskite Solar Cells. Issue 2 (27th November 2022) - Xu, Peng; Xie, Lisha; Yang, Shuncheng; Han, Bin; Liu, Jian; Chen, Jiujiang; Liu, Chang; Jia, Runping; Yang, Mengjin; Ge, Ziyi
Abstract : As a multigroup cross‐linking agent, amino acid derivatives contain different kinds of characteristic functional groups with different characteristics. Aiming at one of the most difficult problems, ionic defects, amino acid derivatives can passivate these defects through their multifunctional groups. Ionic defects (such as organic cations and halogen anions) mostly exist on surface and/or grain boundaries of perovskite films, and amino acid derivatives promote the formation of high‐quality perovskite films by coordinating well with these defects. Herein, the effects of two kinds of amino acids (l ‐arginine and l ‐glutamic acid) with contrastive isoelectric points (pIs) on perovskite film formation, defect passivation mechanism, device efficiency, flexible substrate, and thermal/moisture stability are studied. Efficiency of inverted perovskite solar cells is improved from ≈20% to nearly 23% with additives on rigid substrates. High pI l ‐arginine improves the open‐circuit voltage significantly, while low pI l ‐glutamic acid excels in fill factor and short‐circuit current. More importantly, low pI l ‐glutamic acid shows superior thermal and moisture stability, indicating inherent stronger bonding between l ‐glutamic acid and perovskite. Abstract : Herein, two kinds of amino acids (l ‐arginine and l ‐glutamate) with different isoelectric points (l ‐arginine is 10.76 and l ‐glutamate is 3.22) passivate the defects with different functional groups. Device efficiency is boosted from 20.23% to 22.96% and 22.66%, and humidity stability and thermal stability are also improved at different levels.